Topological–chiral magnetic interactions driven by emergent orbital magnetism - Grytsiuk, S.; Hanke, J. -P.; Hoffmann, M.; Bouaziz, J.; Gomonay, Olena; Bihlmayer, Gustav; Lounis, Samir; Mokrousov, Yuriy; Bluegel, S. (Nature Communications, 2020)
Two hundred years ago, Ampère discovered that electric loops in which currents of electrons are generated by a penetrating magnetic field can mutually interact. Here we show that Ampère’s observation can be transferred to the quantum realm of interactions between triangular plaquettes of spins on a lattice, where the electrical currents at the atomic scale are associated with the orbital motion of electrons in response to the non-coplanarity of neighbouring spins playing the role of a magnetic field. The resulting topological orbital moment underlies the relation of the orbital dynamics with the topology of the spin structure. We demonstrate that the interactions of the topological orbital moments with each other and with the spins form a new class of magnetic interactions − topological–chiral interactions − which can dominate over the Dzyaloshinskii–Moriya interaction, thus opening a path for realizing new classes of chiral magnetic materials with three-dimensional magnetization textures such as hopfions.
CRIS-Team Scopus Importer:2023-03-27